Creativity in Olympic bouldering: exploring the role of climbing level and route previewing - Medernach, J. P.; Augste, C.; Henz, J.; Künzell, S.; Memmert, D.; Sanchez, X. (Journal of Sport & Exercise Psychology, 2025)
In sports, creativity refers to the ability to make decisions that are original and unexpected, yet effective. Given the limited research on climbers` creativity and its underlying mechanisms, this study explored the role of climbing level and route previewing on climbers` creativity and their ability to find creative climbing solutions. Twenty-eight climbers (14 advanced and 14 elite) were tasked with climbing an Olympic boulder that offered two climbing options: an easily identifiable option beyond their climbing levels, and a creative option that, though less identifiable, was feasible for both groups. Results revealed that elite climbers were more successful in completing the boulder, attained higher creativity scores, and more often used the creative option. Despite shorter preview durations, they had fewer holds without fixations and more fixations at key holds of the creative option. Overall, findings indicate that creativity in climbing is associated with skill level and behavior during route previewing.